Postpartum laparoscopic sterilisation: A role in South African healthcare - Deborah Prince; Ramon Aronius; Gerhard Theron (South African Medical Association, 2016)
Objective. To assess the advantages and feasibility of performing postpartum sterilisations laparoscopically in a public healthcare facilityin South Africa (SA).Methods. Retrospective review of postpartum sterilisations between June 2012 and December 2013 at Worcester Hospital, Western Cape,SA. A total of 78 postpartum sterilisations were included in the study (open n=26, laparoscopic n=52). Data analysis was performed usingmeans and medians with range and standard deviations, two-sample Wilcoxon rank sum test, two-sample t-test and Ï‡2 test.Results. It was considered preferable to perform laparoscopic sterilisations than the open procedure on patients with a higher body massindex (BMI). Duration of surgery was shorter in the laparoscopic group, especially in patients with BMI >30, and more patients weredischarged on the same day as surgery in the laparoscopic group. There were fewer overall complications in the laparoscopic group (oddsratio 0.35, 95% confidence interval 0.08 - 1.43).Conclusion. It is feasible to perform postpartum sterilisations laparoscopically in a public healthcare facility in SA. Advantages ofthe procedure are clinically significant and in keeping with international literature. Future research should be undertaken regardingacceptability of the procedure in the study population, laparoscopic training and the improvement of provision of requested postpartumsterilisations in public hospitals.Â